2011
DOI: 10.1186/1475-2840-10-112
|View full text |Cite
|
Sign up to set email alerts
|

PPARγ Pro12Ala and ACE ID polymorphisms are associated with BMI and fat distribution, but not metabolic syndrome

Abstract: BackgroundMetabolic Syndrome (MetS) results from the combined effect of environmental and genetic factors. We investigated the possible association of peroxisome proliferator-activated receptor-γ2 (PPARγ2) Pro12Ala and Angiotensin Converting Enzyme (ACE) I/D polymorphisms with MetS and interaction between these genetic variants.MethodsThree hundred sixty four unrelated Caucasian subjects were enrolled. Waist circumference, blood pressure, and body mass index (BMI) were recorded. Body composition was estimated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
29
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 44 publications
5
29
0
1
Order By: Relevance
“…21 Similarly, Passaro et al showed that subjects with different polymorphisms in the ACE gene did not show significant variability in BMI. 22 The frequency of the ACE deletion/deletion genotype among hypertensive overweight/obese individuals in the current study (19.33%) was similar to that found among an overweight Pakistani population (18.00%). 8 The frequency of the ACE insertion/ insertion genotype in the hypertensive overweight/ obese group of the current study (27.33%) was similar to that found among obese Pakistani individuals (26.00%); however, it was lower than the frequency found among overweight Pakistanis (32.00%).…”
Section: Discussionsupporting
confidence: 84%
“…21 Similarly, Passaro et al showed that subjects with different polymorphisms in the ACE gene did not show significant variability in BMI. 22 The frequency of the ACE deletion/deletion genotype among hypertensive overweight/obese individuals in the current study (19.33%) was similar to that found among an overweight Pakistani population (18.00%). 8 The frequency of the ACE insertion/ insertion genotype in the hypertensive overweight/ obese group of the current study (27.33%) was similar to that found among obese Pakistani individuals (26.00%); however, it was lower than the frequency found among overweight Pakistanis (32.00%).…”
Section: Discussionsupporting
confidence: 84%
“…Chehaibi et al (2014) found that the T allele carriers had lower prevalence rates of diabetes mellitus and TG levels than C allele carriers (OR = 0.575). These research results correspond to our findings; however, Passaro et al (2011) could not discern an obvious correlation between PPARγ polymorphisms and MS.…”
Section: Discussionsupporting
confidence: 91%
“…The relationship between these factors and genotype and phenotype merits attention. For example, Passaro et al 33 reported that ACE DD subjects had a higher BMI and fat mass. Min et al 34 reported that ACE II genotype was associated with a higher blood pressure.…”
Section: Discussionmentioning
confidence: 99%